2014
DOI: 10.1088/2053-1583/1/3/034002
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of graphene foam supported carbon nanotube/polyaniline hybrids for high-performance supercapacitor applications

Abstract: A large-scale, high-powered energy storage system is crucial for addressing the energy problem. The development of high-performance materials is a key issue in realizing the grid-scale applications of energystorage devices. In this work, we describe a simple and scalable method for fabricating hybrids (graphenepyrrole/ carbon nanotube-polyaniline (GPCP)) using graphene foam as the supporting template. Graphene-pyrrole (G-Py) aerogels are prepared via a green hydrothermal route from two-dimensional materials su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
1
8
1
2
Order By: Relevance
“…The specific capacitance of NGF calculated from these CV curves at scan rates of 2 and 50 mV/s is 150 and 96.3 F/g, respectively, which means a good capacitance retention of 64.2% as the scan rate is changed from 2 to 50 mV/s. Figure b shows the C s of the NGF electrode generally deceases with increasing CV scan rate, which is similar to the behavior of other graphene materials. ,,, …”
Section: Results and Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The specific capacitance of NGF calculated from these CV curves at scan rates of 2 and 50 mV/s is 150 and 96.3 F/g, respectively, which means a good capacitance retention of 64.2% as the scan rate is changed from 2 to 50 mV/s. Figure b shows the C s of the NGF electrode generally deceases with increasing CV scan rate, which is similar to the behavior of other graphene materials. ,,, …”
Section: Results and Discussionsupporting
confidence: 72%
“…Figure 6b shows the C s of the NGF electrode generally deceases with increasing CV scan rate, which is similar to the behavior of other graphene materials. 5,33,43,44 For comparison, GF without N-doping was also fabricated by the CVD method, 45,46 and their electrochemical capacitive performance was studied at the same experimental conditions. X-ray CT of the GF in our recent work 45 shows similar interconnected hollow strut structure as the NGF studied here.…”
Section: Resultsmentioning
confidence: 99%
“…The ternary hybrid material rGO/MnO 2 /PANI20 shows poor capacitive performance compared to rGO/MnO 2 /PANI5 and rGO/MnO 2 /PANI10 (in ESI† Figure S5(c‐d)). The best specific capacitance values given by the ternary composite described here are much better than the previous reported values for rGO/MnO 2 /PANI based composite materials in the literature,(ESI†, Table ST1). This result clearly demonstrates that the ordered whisker like structure can enhance the utilization of the electrode material by increasing the electrochemical accessibility of electrolyte through the material.…”
Section: Resultscontrasting
confidence: 44%
“…To address such issues, considerable research efforts have been made to improve the conductivity of MnO 2 ‐based electrodes with simultaneous optimization of their electrochemical performance through exploring hybrid composite structures with highly conducting materials like metal nanostructures, conducting polymers, carbon nanotubes and graphene . Among various hybrid materials developed so far, graphene/PANI, PANI/MnO 2 , graphene/MnO 2 binary and graphene/MnO 2 /PANI ternary nanostructure based SCs electrode materials are found to be promising for large scale energy storage system due to their low cost, scalable synthesis and processability ,. It has been reported that the electrochemical capacitance performance of MnO 2 /graphene composite electrodes can be further improved significantly by wrapping MnO 2 /graphene sheets three dimensionally with conducting polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Besides graphene, such twodimensional materials as monolayer phosphorus and monolayer transition-metal dichalcogenides (TMDC) exhibit many novel physical properties which do not exist in their bulk counterparts. The two-dimensional materials are promising for applications in many fields, such as field-effect transistors 5,6 , phototransistors 7,8 , p-n junctions 9,10 , supercapacitors 11,12 , and batteries 13,14 .…”
Section: Introductionmentioning
confidence: 99%